Comparison of the microbial community and flavor compounds in fermented mandarin fish (Siniperca chuatsi): Three typical types of Chinese fermented mandarin fish products. (June 2021) - Wang, Yueqi; Shen, Yingying; Wu, Yanyan; Li, Chunsheng; Li, Laihao; Zhao, Yongqiang; Hu, Xiao; Wei, Ya; Huang, Hui
Graphical abstract: Highlights: Microbiota and flavor from three fermented mandarin fish products was conducted. Microbial composition was significantly different among three samples. Characteristic flavor substances explored in three products. Correlative network model elucidated microbe correlations with flavor compounds. Three genera in particular were good associated with key flavor components. Abstract: Fermented mandarin fish have been receiving attention from consumers due to their nutritional value and specific flavor. Microbial diversity in fermented mandarin fish has an important impact on their flavor and quality. However, little is known about the microbiome and the differences among different products. In this study, the bacterial profiles and flavor compounds in three typical fermented mandarin fish products were investigated and compared, and a correlation network was used to explore the potential relationship between microorganisms and flavor. Bacterial community analysis demonstrated clear differences in microbiota among the HF-, MF-, and OF-fermented mandarin fish products. Psychrilyobacter, Fusobacterium, and Vibrio were the most dominant in the HF-, MF-, and OF-fermented products, respectively. In addition, 14, 12, and 4 flavor substances (relative odor activity value, ROAV ≥ 1) were detected in the muscles from the central dorsal and ventral sides of the three samples, respectively. Several bacteria correlated with the production of important flavor compounds, and three genera ( Arcobacter, Psychrilyobacter, and Shewanella ) were the primary microorganisms contributing to more than six characteristic flavor compounds in fermented mandarin fish products. Therefore, the study's systematic method allows identificating important microbes and characteristic volatile flavor compounds in fermented mandarin fish and provides new insights into the relationship between microorganisms and flavor.